2023
DOI: 10.3389/fendo.2023.1188487
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and metabolic syndrome and its components

Abstract: Background and aimThe association between Helicobacter pylori (H. pylori) infection and metabolic syndrome (MetS) has been studied previously; however, the results remain controversial, which could be partly due to the different criteria used for defining MetS. We adopted five MetS criteria to provide better understanding of the association between H. pylori infection and MetS.MethodsPhysical examination data of 100,708 subjects were obtained from January 2014 to December 2018. MetS was defined based on five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…25 Another more recent retrospective cross-sectional study in China reinforced these associations within the same population, utilizing five diagnostic criteria simultaneously (IDF, ATP III, JIS, CDS, and CDS DM). 26 In summary, the evidences support the positive associations between H. pylori infection and metabolic syndrome, as defined by multiple diagnostic criteria.…”
Section: Obesitymentioning
confidence: 74%
See 1 more Smart Citation
“…25 Another more recent retrospective cross-sectional study in China reinforced these associations within the same population, utilizing five diagnostic criteria simultaneously (IDF, ATP III, JIS, CDS, and CDS DM). 26 In summary, the evidences support the positive associations between H. pylori infection and metabolic syndrome, as defined by multiple diagnostic criteria.…”
Section: Obesitymentioning
confidence: 74%
“…Numerous studies have investigated the association between H. pylori infection and insulin resistance, but the results remain conflicting. 26,50,51 A previous meta-analysis of 22 case-control studies involving 206,911 participants, covering the period from 1991 to January 2021, quantified a combined OR of 1.54 (95% CI: 1.19-1.98) for the association between H. pylori infection and insulin resistance. 25 In cohort studies, this meta-analysis determined a summarized HR of 1.31 (95% CI: 1.13-1.51) for the occurrence of insulin resistance in individuals with H. pylori infection.…”
Section: Insulin Resistancementioning
confidence: 99%
“…Therefore, the search for new therapeutic strategies against H. pylori infection is highly significant [60][61][62][63][64]. Nevertheless, there is controversy about the need for H. pylori eradication treatment when patients do not manifest any relevant symptoms due to the fact that it has been observed that in some cases the eradication of H. pylori is associated with the rise of other pathologies such as metabolic syndrome, gastroesophageal reflux disease (GERD) and its consequences, including esophageal and gastric cardia glandular malignancies [65][66][67]. In children, eradication is not recommended and other guidelines must be followed in order to manage the infection [68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence highlights a strong connection between MetS and active H. pylori infections, with both disorders appearing to mutually influence their pathophysiology [11]. This infection is associated with MetS [12], and its eradication positively impacts MetS components [13]. Furthermore, H. pylori is a risk factor for CVD, and its eradication is considered safe from a cardiac standpoint [14].…”
Section: Introductionmentioning
confidence: 99%